Singlet Fission in Enantiomerically Pure Pentacene Dimers - Papadopoulos, Ilias; Gao, Yueze; Hetzer, Constantin; Tykwinski, Rik R.; Guldi, Dirk Michael (Chemphotochem, 2020)
Singlet fission (SF), that is, producing two triplet excited states (T-1+T-1) from a single singlet excited state (S1S0), has the potential to surpass the thermodynamic Shockley-Queisser limit for solar cells of 33 %. Of great relevance for singlet fission is the (S1S0)-to-(1)(T1T1) transformation as it is the key step in driving the efficiency of SF. In the current study, we focus on the control over intramolecular interactions in enantiomerically pure platinum linked pentacene dimers, (S,S)- and (R,R)-cis-Pt. Despite the internal heavy-atom effect stemming from the presence of the Pt-centered linkers, (S,S)- and (R,R)-cis-Pt undergo quantitative and solvent dependent formation of (1)(T1T1). Implicit is an enantiomer-independent SF mediation by means of a virtual CT intermediate in a superexchange mechanism. With the help of steady-state and time-resolved spectroscopic techniques, a kinetic model is developed to describe the entire deactivation pathway following photoexcitation of (S,S)- and (R,R)-cis-Pt.
CRIS-Team WoS Importer:2020-05-02